(untitled) (ModaPalavra e-periódico, 2025)
The article analyzes the intersection between fashion and politics through the figure of Erika Hilton, a federal deputy for PSOL-SP, highlighting how she uses fashion to promote her gender identity and activism. The case study, based on an interview with Ela magazine from O Globo for International Women’s Day, explores issues of inclusion and diversity while presenting Erika in a photo shoot with a fashion editorial feel. The research is classified as basic, qualitative and descriptive, using bibliographic research and the intersectional roulette approach, together with Ervin Goffman’s frameworks of meanings. The results reveal the contradictions between the use of luxury brands and social struggles, showing how fashion can be a means of inclusion but also perpetuate exclusions.